Pre-treatment of grain for ethanol production during storage - Almgren, Ingrid (SLU/Dept. of Microbiology, 2010)
Ethanol for automotive purposes is an issue much debated and researchers disagree about the benefits of bioethanol. Converting energy-rich crops into ethanol suitable as motor fuel is a complex process and continuous development and improvements of processes and material used are important steps in the work of developing environmental friendly fuels. Grain is usually preserved by drying which consumes a lot of energy. Alternative storage of high-moisture grain in airtight storage systems reduce the energy required to produce bioethanol and studies have also shown that ethanol yields are increased more than 10% in ethanol fermentations of moist grain compared to dry. Airtight storage is often not perfectly airtight so biocontrol agents are necessary in order to preserve the grain. The yeast Pichia anomala has anti-microbial activity and inhibits mould growth in airtight stored moist grain with some air leakage and is therefore an attractive alternative for biocontrol.